LIQUORICE BEVERAGE EFFECT ON THE PHARMACOKINETIC PARAMETERS OF ATORVASTATIN, SIMVASTATIN, AND LOVASTATIN BY LIQUID CHROMATOGRAPHY-MASS SPECTROSCOPY/MASS SPECTROSCOPY - Abu dayyih, Wael A; Mallah, Eyad M; Al-ani, Israa H; A Arafat, Tawfiq (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The objective of this study is to examine the effects of pre-consumption of freshly prepared liquorice beverage (4 ml/kg) on the pharmacokinetic (PK) parameters of (80 mg/kg) oral dose of atorvastatin, simvastatin, and lovastatin in healthy rats plasma. Methods: A simple, rapid, and applicable analytical method was developed for the determination of each statin in rats' plasma. This method uses liquid chromatography-mass spectroscopy/mass spectroscopy. The mobile phase composed of methanol and formic acid in water and glimepiride as an internal standard. 108 rats were used in this study. Liquorice juice was given, and then each of the statins was given to test groups and liquorice only to the control groups, and then plasma samples were withdrawn on specific time schedule then PK analysis was performed. Results: The analytical method showed acceptable linearity, recovery, precision, and accuracy. Administration of liquorice resulted in a significant increase in maximum concentration in plasma (C ) of the three statins, also the area under plasma level-time curves (area under curve) was increased significantly. Moreover, the bioavailability of the drugs. On the other hand, the elimination of the three drugs showed no great changes, which suggests an interaction between liquorice and the transporting system of statins on the gut and biliary wall. max Conclusion: Consumption of liquorice results in increase bioavailability of atorvastatin, simvastatin, and lovastatin. Keywords: Liquorice, Atorvastatin, Liquid chromatography-mass spectroscopy/mass spectroscopy, Simvastatin, Lovastatin, Pharmacokinetic parameters.